1972
DOI: 10.1002/jmor.1051360402
|View full text |Cite
|
Sign up to set email alerts
|

Mastication in the little brown bat, Myotis lucifugus

Abstract: The masticatory apparatus of the vespertilionid bat Myotis lucifugus appears generalized. Principal modifications for more efficient trituration have involved accessory tooth cusps. Chewing strokes pass through orbits (up to 7/sec) involving translations along and rotation about three axes. Direction of chewing typically reverses by at least the fifth or sixth consecutive orbit. Reversal involves modification of the downstroke at varying positions along its course. Compared to certain other bats, which do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…The tendency of the human medial pterygoid muscles to alternate their activity in all phases of the masticatory stroke other than early closing (when both are active although unequally) and sometimes late in the intercuspal position, is reminiscent of that reported by Kallen and Gans (1972) for Myotis. Their data differ slightly in that ipsilateral activity begins a little later (as the jaw swings medially into intercuspation) and lasts a little longer (as the jaw moves out of intercuspation); another small difference is the apparent consistent absence of a late burst from the contralateral muscle in the intercuspal position, a feature which appeared in some of our subjects.…”
mentioning
confidence: 85%
“…The tendency of the human medial pterygoid muscles to alternate their activity in all phases of the masticatory stroke other than early closing (when both are active although unequally) and sometimes late in the intercuspal position, is reminiscent of that reported by Kallen and Gans (1972) for Myotis. Their data differ slightly in that ipsilateral activity begins a little later (as the jaw swings medially into intercuspation) and lasts a little longer (as the jaw moves out of intercuspation); another small difference is the apparent consistent absence of a late burst from the contralateral muscle in the intercuspal position, a feature which appeared in some of our subjects.…”
mentioning
confidence: 85%
“…Published electromyographic data suggest that all jaw closer muscles are indeed maximally or near maximally recruited during biting on hard or tough foods (Kallen and Gans, 1972;De Gueldre and De Vree, 1988). Note, however, that maximal activation does not necessarily imply force generation.…”
Section: A Herrel and Othersmentioning
confidence: 98%
“…However, as already mentioned, galagos have ratios well in excess of 1:1, and similarly high W/B superficial masseter ratios occur in dogs (which also lack fusion; Dessem, 1989). Likewise, EMG analyses of bats have shown that Myotis, a vespertilionid with a patent symphysis, appears to exhibit higher W/B ratios than Pteropus, a pteropodid with an ossified symphysis (Kallen and Gans, 1972;de Gueldre and de Vree, 1984, 1988, 1990. Therefore, the extent to which any of these species are typical of mammals with unfused symphyses remains unclear, and will require comparable in vivo data for additional taxa.…”
mentioning
confidence: 97%